Keterkaitan Alexithymia dengan Perilaku Agresif pada Remaja Laki-Laki - Siti Nurfitria; Iin Inayatul Machsunah (Proceedings of The ICECRS, 2019)
In 2018, KPAI noted that 84% of students in Indonesia had experienced violence at school. The research conducted by Jannah (2018) on early adolescents at Surabaya A Junior High School revealed that 76% of students had hit, 66% had fought, 46% had damaged items when angry, 90% had been hostile, 84% were angry and indicated adolescents tend to be prone to aggressive behavior. Adolescents who are male have a tendency to behave aggressively higher when compared to women (Santrock, 2007). The development of impulsive aggression involves emotional processes (Teten et al, 2008). Emotional states during adolescence are characterized by unstable and turbulent emotions, so that the mood can change quickly. Teenagers are said to have reached emotional maturity if they do not "blow up" their emotions in front of other people but wait for a more appropriate time and place to express their emotions in ways that are more acceptable. Adolescents whose emotions mature provide stable emotional reactions, do not change from one emotion or mood to another. The difficulty of reacting to emotions is called alexithymia. According to Sadock & Virginia (2010), alexithymia is a person's inability to describe or have difficulty describing or being aware of his emotions or mood. Goleman (2017) states that emotional blindness will cause several disadvantages including aggressive behavior. Research shows that high alexithymia levels are associated with high aggressive behavior and impulsive behavior (Teten et al, 2008). Salminen et al. (1998) stated that men were more likely to be not expressive in conveying emotions so that the possibility of alexithymia occurring in men was more than women. Based on the theoretical study above, there is an association between alexithymia and aggressive behavior in male adolescents.